2011
DOI: 10.4193/rhino10.293
|View full text |Cite
|
Sign up to set email alerts
|

Revison endonasal dacryocystorhinostomies: analysis of 44 procedures

Abstract: Purpose: To determine the success rate of revision endoscopic dacryocystorhinostomies (DCR) and to analyse 44 revision DCRs. Methods: The operative and postoperative data were collected in 44 revision DCRs. The corrections of associated structural anatomic alterations were performed during the surgery (resection of the scarr, the bone window creating, resection of the head of the middle turbinate, septoplasty, ethmoidectomy etc.) and the intubation was performed in all cases. Results: The follow-up interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We had about an 81% success rate in the nonmitomycin group 15 months after surgery. Kominek et al 14 reported an 84% success rate in nonmitomycin revision endoscopic DCR in their cohort of 44 patients. Korkut et al 15 reported an 84% success rate in revision endoscopic DCR without mitomycin as well.…”
Section: Discussionmentioning
confidence: 97%
“…We had about an 81% success rate in the nonmitomycin group 15 months after surgery. Kominek et al 14 reported an 84% success rate in nonmitomycin revision endoscopic DCR in their cohort of 44 patients. Korkut et al 15 reported an 84% success rate in revision endoscopic DCR without mitomycin as well.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, minimally invasive procedures such as endoscopic DCR and transcanalicular diode lasers have been preferred (26)(27)(28)(29)(30)(31). DSG is also useful in assessing the success of these techniques (32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%